M. bovis infection in pigs: Improvement of the γ-IFN assay efficiency in this species using a maintenance medium. (January 2018) - Gerace, Elisabetta; Mandanici, Francesca; Pasquali, Paolo; Falduto, Maria; Vitale, Maria; Di Marco Lo Presti, Vincenzo; Amato, Benedetta
Abstract: The interferon-gamma (IFN-γ) test measures cell mediated immune response (CMI) during the early stages of tuberculosis infection. Although Bovine Tuberculosis (BT) spread in feral pigs is widely documented in literature, the effectiveness of IFN-γ in this species has been only recently reported. One of the major obstacle of this assay is that whole blood samples should be stimulated with purified protein derivative (PPD) cocktail within 8 h from the blood sampling. This study set up a defined broth culture in which lymphocytes, the cell population predominantly responsible for IFN-γ production, are maintained in a steady-state and their vitality is preserved. The IFN-γ production measured from the samples added with the maintenance medium and stored at 4 °C was similar to the enzyme-linked immunosorbent assay (ELISA) optical density values obtained from the same assay performed within 8 h from sampling.